Perancangan Game Interaktif Android Belajar Huruf Hijaiyah Al-Dhaki Berbasis Apk Dengan Adobe CC Animate 2018 - John John; Ria Eka Sari; Joko Rahmat (Filosofi : Publikasi Ilmu Komunikasi, Desain, Seni Budaya, 2025)
The introduction of hijaiyah letters in early childhood is an important stage in building the basis for learning the Qur'an. This research aims to develop an interactive game called Al-Dhaki which is designed to help parents and early childhood education teachers in introducing hijaiyah letters to children in an interesting and effective way. This game is designed using quantitative research methods to analyze user needs, with a 5W+1H approach (What, Why, Who, When, Where, and How) in data collection and analysis. The results of the study show that game-based interactive learning media can increase children's interest in learning and simplify the process of recognizing hijaiyah letters. Al-Dhaki is developed in the form of an application file (APK) that can be installed on Android devices, making it easily accessible to users. The game is equipped with interactive features, such as sounds, animations, and simple quizzes, to increase children's engagement in learning. With the presence of Al-Dhaki, it is hoped that the process of recognizing hijaiyah letters will be more fun and effective, as well as providing practical solutions for parents and PAUD teachers in supporting the development of religious literacy in early childhood.